2009
DOI: 10.1016/j.virol.2008.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Tomato spotted wilt virus nucleocapsid protein interacts with both viral glycoproteins Gn and Gc in planta

Abstract: Recently, the Tomato Spotted Wilt Virus (TSWV) Gn and Gc glycoproteins were shown to induce the formation of (pseudo-) circular and pleomorphic membrane structures upon transient expression in plant cells. Furthermore, when singly expressed, Gc retains in the ER, while Gn is able to further migrate to the Golgi. Upon co-expression, Gn rescues Gc and co-migrates to the Golgi complex. Here, we have studied the behavior of the glycoproteins in the presence of the viral nucleocapsid (N) protein and in vivo analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 22 publications
2
78
0
1
Order By: Relevance
“…To mediate the packaging of viral RNA, an enveloped virus that lacks a matrix protein instead requires a direct interaction between the intraviral domains of the envelope-embedded glycoproteins and the RNP. The most thoroughly characterized examples of this type of direct glycoprotein-RNP interaction have been described for the families Coronaviridae, Flaviviridae and Togaviridae (Lo et al, 1996;Narayanan et al, 2000;Sturman et al, 1980) and, while this is the first report of glycoprotein-RNP interaction for a virus in the genus Hantavirus, it has already been reported for other members of the family Bunyaviridae (Liu et al, 2008;Overby et al, 2007a;Ribeiro et al, 2009;Snippe et al, 2007). In addition, this interaction has recently been identified with the TULV Gn-CT and N protein using recombinant proteins (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…To mediate the packaging of viral RNA, an enveloped virus that lacks a matrix protein instead requires a direct interaction between the intraviral domains of the envelope-embedded glycoproteins and the RNP. The most thoroughly characterized examples of this type of direct glycoprotein-RNP interaction have been described for the families Coronaviridae, Flaviviridae and Togaviridae (Lo et al, 1996;Narayanan et al, 2000;Sturman et al, 1980) and, while this is the first report of glycoprotein-RNP interaction for a virus in the genus Hantavirus, it has already been reported for other members of the family Bunyaviridae (Liu et al, 2008;Overby et al, 2007a;Ribeiro et al, 2009;Snippe et al, 2007). In addition, this interaction has recently been identified with the TULV Gn-CT and N protein using recombinant proteins (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…The peptide-bound proteins were separated by SDS-PAGE (10 % gel) and detected by autoradiography (in vitro-translated N) or immunoblotting using rabbit antiserum to PUUV N protein (RNP). et al, 2007a;Ribeiro et al, 2009;Snippe et al, 2007). In addition, this interaction has recently been identified with the TULV Gn-CT and N protein using recombinant proteins (Wang et al, 2010).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…These vRNP complexes perform genome RNA replication and viral mRNA transcription. Moreover, N protein has been shown to interact with Gn/Gc protein and it has therefore been suggested that the N protein plays a crucial role in viral encapsidation (Ribeiro et al, 2009). Overall, the N protein is an important factor in the TSWV life cycle.…”
Section: Introductionmentioning
confidence: 99%